Effect of Adenosine 5´ Triphosphate (ATP) and Incubation Time on Frozen Thawed Buffalo Bull Spermatozoa - Hanif, Misbah; Ahmad, Ejaz; Naseer, Zahid; Akhtar, Muhammad Saleem; Ahmad , Tanveer; Hussain, Tanveer; Murtaza , Saeed (The Indian Journal of Animal Reproduction, 2023)
The present study was aimed to determine the effect of ATP dose rate on longevity, motility, and viability of frozen-thawed buffalo bull’s sperm. For this purpose, 20 frozen semen straws of four different buffalo bulls were obtained from a private semen production unit (Al-Hiawan Sires, Sahiwal). The experiment was replicated four times. In each replicate, four frozen straws of the same bulls were thawed and pooled. After evaluating the motility, the pooled frozen-thawed sample was aliquoted into three separate tubes containing 0 (control), 1-, or 2-mM concentrations of ATP. Afterward, each aliquot was incubated at 37oC for 4 hrs. The sperm motility, viability, and membrane integrity were observed at various time points (10 min., 1hr, 2hr, and 4hr) during the incubation period of four hrs. It was observed that progressive motility and most of the motion kinematic parameters were greater (P
Keywords: Buffalo bull; ATP; Sperm; Post-thaw